Is the Training Intensity in Phase Two Cardiovascular Rehabilitation Different in Telehealth versus Outpatient Rehabilitation? - Batalik, Ladislav; Pepera, Garyfallia; Papathanasiou, Jannis; Rutkowski, Sebastian; Líška, David; Batalikova, Katerina; Hartman, Martin; Felšőci, Marián; Dosbaba, Filip (Journal of clinical medicine, 2021)
Telehealth cardiac rehabilitation (CR) is a feasible and effective alternative to conventional outpatient CR. Present evidence is limited on the comparison of exercise intensity adherence in telehealth and outpatient CR. The purpose of the study was to evaluate and compare training intensity adherence through 12-week phase II CR in telehealth and outpatient CR. A sample of 56 patients with coronary artery disease (CAD) with a mean age of 56.7 ± 7.1 entering comprehensive secondary prevention phase II was randomized into telehealth CR (n = 28) and control outpatient CR (n = 28) groups. The primary outcome was a comparison of training intensity adherence in both CR models and heart rate (HR) response from individual CR sessions, expressed by the HR reserve percentage. As a result, the parameter HR reserve percentage as the total average of the training intensity during the telehealth intervention and the outpatient CR did not differ statistically (p = 0.63). There was no death case, and all severe adverse cases required medical admission throughout an exercise training session in study subjects in both groups. This research evidence demonstrated that the telehealth CR model is similar in training intensities to the conventional outpatient CR in CAD patients with low to moderate cardiovascular risk.
Keywords: outpatient rehabilitation; physical exercise; coronary artery disease; heart rate disease; telerehabilitation; telehealth; cardiovascular rehabilitation